(untitled) (Research, Society and Development, 2024)
Obesity is defined as excess adiposity, resulting from a prolonged state of positive energy balance capable of causing a state of chronic inflammation in individuals, with subsequent deposition of ectopic fat in the kidney, as well as the storage of lipids in the breast. kidney, causing renal lip toxicity. The main objective of the present study is to relate the presence of kidney damage with obesity, using microalbuminuria (MA) research, considered an early marker of glomerular damage. Methodology: This is a clinical, cross-sectional, prospective study, with 100 patients with a body mass index (BMI) ≥ 30 kg/m², who were being monitored for bariatric surgery. The urine strip test was used to quantify albumin in urine, with albuminuria defined as values greater than 30 mg of albumin per gram of creatinine. Furthermore, epidemiological data were collected with the aim of correlating them with albuminuria. Results: The statistical analysis carried out in this study was based on a variety of statistical methods, based on data from 100 patients participating in the research, where 22% of patients presented some degree of albuminuria, among them, around 63.6 % of them reported not having any type of previous comorbidity. Conclusion: The present study demonstrates a possible relationship between the presence of obesity and the progression of kidney damage, and it is important to highlight that more than half of the patients with changes in the albuminuria test reported the absence of previous pathologies.